Switchable light vs. acid-induced transformations of complex framework compounds at room temperature. Issue 9 (21st April 2022) - Kobzev, Maxim S.; Titov, Alexander A.; Borisova, Tatiana N.; Voskressensky, Leonid G.; Varlamov, Alexey V.; D'Alterio, Massimo Christian; Petrone, Alessio; Luque, Rafael; Talarico, Giovanni
Abstract : A novel protocol for the synthesis of complex framework compounds containing a VCP fragment is presented by means of UV conversion of CP derivatives at r.t., providing high yields of target products in an unprecedented atom economical reversible step. Abstract : A novel and original protocol for the preparation of complex framework compounds containing a vinylcyclopropane (VCP) fragment is presented by means of UV conversion of cyclopentene (CP) derivatives under standard conditions, providing high yields of target products in an unprecedented atom economical reversible step. The reverse transformation of compounds with vinylcyclopropyl moieties into CP derivatives takes place in the presence of trifluoroacetic acid at room temperature. A one-pot approach for the synthesis of VCPs from the corresponding benzoazacyclic allenes has also been developed and the mechanisms of mutual rearrangements of both VCP and CP have been rationalized by DFT calculations.